Financial Performance of State Electricity Boards in the Seventh Plan Period August, 1985 - Planning Commission (Planning Commission, 1985)
The document assesses the financial performance of State Electricity Boards (SEBs) during India’s Seventh Plan (1985–90), following prior analysis of the Sixth Plan. SEBs faced substantial commercial losses of ₹4,472 crores in the Sixth Plan, with projected losses escalating to ₹11,757 crores in the Seventh Plan due to operational inefficiencies and growing power purchase costs. Key performance metrics, including plant load factor, auxiliary consumption, and transmission and distribution losses, are expected to improve modestly. Electricity tariffs are projected to rise variably across states to ensure statutory returns, while internal resource deficits are estimated at ₹1,469 crores. High debt, interest obligations, and increased reliance on purchased power compound financial pressures. The report underscores the need for improved operational efficiency, strategic pricing, and disciplined financial management to achieve SEBs’ viability and fiscal stability.
Planning Commission (Power and Energy Division)
Planning Commission (Power and Energy Division)
Keywords: State Electricity Boards; Seventh Plan; Commercial Losses; Power Generation; Transmission Losses; Auxiliary Consumption; Electricity Tariffs; Financial Deficits; Operational Efficiency; Purchased Power